Displasia mesenquimal placentaria - Romero Rojas, Nery (2023)
Placental mesenchymal dysplasia is a rare entity, confused with ultrasound and macroscopy with partial mole due to vesicular lesions and the presence of a fetus. Microscopy reveals hydropic trunk villi with great mesenchymal hyperplasia and prominent vascular lesions but without hyperplasia of the trophoblastic epithelium. The fetus, usually female, may be normal or present malformations, tumors or chromosomopathies. We present the study of four cases of placental mesenchymal dysplasia; three first-pregnancies, aged 39 and 20, and a second-pregnancy, aged 26. The oldest in the third trimester presented with preeclampsia and a female stillbirth with pulmonary and splenic anomalies, the other two presented vaginal bleeding and pelvic pain and one case was a finding in prenatal control at 8 weeks of gestation. In three cases, fetus and embryo were observed, two of them had a necropsy.